In vivo study of the action of a topical anti-inflammatory drug in rat teeth submitted to dental bleaching - Benetti, Francine [UNESP]; Briso, André Luiz Fraga [UNESP]; Ferreira, Luciana Louzada [UNESP]; Carminatti, Marina [UNESP]; Álamo, Larissa [UNESP]; Ervolino, Edilson [UNESP]; Dezan-Júnior, Eloi [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (FapUNIFESP (SciELO), 2018)
Bleaching gel containing hydrogen peroxide (H 2 O 2 ) cause damages in pulp tissue. This study investigated the action of a topical anti-inflammatory, the Otosporin®, in rats’ bleached teeth with the null hypothesis of which the Otosporin® is no able to minimize the pulp inflammation that bleaching gel generates. The rat’s molars were divided into groups: BLE: bleached (35% H 2 O 2 concentration /single application of 30 min); BLE-O: bleached followed by Otosporin® (10 min); and control: placebo gel. In the second day after dental bleaching, the rats were killed, and the jaws were processed for hematoxylin-eosin and immunohistochemistry analysis for tumor necrosis factor alpha (TNF-α), interleukin (IL)-6 and IL-17. The data collected were subjected to Kruskal-Wallis and Dunn statistical tests with at a 5% level of significance (p<0.05). The BLE group had moderate to strong inflammation in the occlusal third of the coronary pulp, with necrotic areas; and BLE-O, mild inflammation (p<0.05). There was a significant difference in the occlusal and middle thirds of the coronary pulp between the BLE with BLE-O and control groups (p<0.05). There was no difference in the cervical third (p>0.05). The BLE group had a high immunoexpression of TNF-α than BLE-O and control groups (p<0.05), with moderate and mild immunoexpression, respectively. Regarding IL-6 and IL-17, the BLE group had higher immunoexpression than control (p<0.05); the BLE-O was similar to the control (p>0.05). The topical anti-inflammatory Otosporin® can reduce pulp inflammation after dental bleaching in the rat teeth.
Keywords: Anti-inflammatory agent; Dental pulp; Hydrogen peroxide; Tooth bleaching